Establishment of a shellfish model farm : a case study in Sg. Jarum Mas, Perak, Malaysia - Md. Nordin, Wan Norhana; Mahyudin, Nor Ainy; Othman, Mohd Shahwahid; Abd. Latiff, Faazaz; Ismail, I.; Yusri, A. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
This study evaluates the sanitary and physico-chemical quality of Sg. Jarum Mas shellfish waters in order to establish its suitability as a model farm. Seawater and shellfish from nine stations (4 shellfish harvesting waters, 4 surrounding waters and 1 control site) were collected and analyzed monthly from September 2004 - September 2005. The results show that shellfish harvesting waters in Sg. Jarum Mas can be classified as 'approved' and 'conditionally approved'. Hepatitis A virus was not detected in any of the shellfish examined. Dinophysis caudata and Pseuodonitzshia spp. were the most common harmful alga species observed. Harmful species that are known to produce toxins and cause shellfish poisoning such as Alexandrium spp., Gymnodinum spp., Pyrodinium sp. and Prorocentrum spp. were not detected. The physico-chemical characteristics of shellfish waters in Sg. Jarum Mas imply that they are suitable for aquaculture activity of moderately tolerant species such as shellfish.